A Portrait of Male's Struggle Quality in William Somerset Maugham's Liza Of Lambeth (Universitas Islam Negeri Sunan Ampel Surabaya, 2016)
This article attempts to analyze William Somerset Maugham's novel entitled Liza of Lambeth. This novel tells about Liza who is loved by two men, Jim and Tom, who want Liza as their lover, so they make some efforts to get her. This article focuses on analyzing the male characters' struggle to attract Liza. The aims of this article are to describe the main characters’personality and to reveal the quality of the male characters' struggle in the novel. Dealing with the focus of the study, this study uses the theory of character as the basic concept to lead the further analysis using existentialism theory to depict the male characters' struggle, and it is supported by the theory of interpersonal attraction. For the last, the main point of this study will be directed to the theory of deconstruction which reveals that everyone who works hard is not guaranteed to be a success. Furthermore, this paper also tries to reflect some points with Islamic values.